2014
DOI: 10.1016/j.chb.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Social media self-efficacy and information evaluation online

Abstract: a b s t r a c tThis study introduces the concept of social media self-efficacy, or a person's perceived ability to reach desired outcomes in the social media environment, and examines the relationship between social media self-efficacy and how people evaluate information found online. Results of a survey of a representative sample of adult Internet users in the United States (N = 3568) indicate that users with higher social media self-efficacy find information shared via social media to be more trustworthy tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 48 publications
2
102
0
2
Order By: Relevance
“…However these successes depended on gaining critical mass and problem solving efficiency achieved through persistent substantial voluntary time commitment of members who initially took on the leading roles. These members clearly had a high level of social media self-efficacy [45] and as leaders engaged not only in Facebook activities but also in parallel in prolonged involvements in the physical environments aimed at connected actions for community benefit. These were repeatedly and transparently reported via Facebook with adjoining open invitations for wider engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However these successes depended on gaining critical mass and problem solving efficiency achieved through persistent substantial voluntary time commitment of members who initially took on the leading roles. These members clearly had a high level of social media self-efficacy [45] and as leaders engaged not only in Facebook activities but also in parallel in prolonged involvements in the physical environments aimed at connected actions for community benefit. These were repeatedly and transparently reported via Facebook with adjoining open invitations for wider engagement.…”
Section: Discussionmentioning
confidence: 99%
“…For many, with high levels of social media use, they come to depend on social media for information seeking. These people may be described as having social media self-efficacy [19], they find the opinions of those on social media to be trustworthy and they rely on them when making decisions in their lives. Research into the influence of social interactions with others on social media is important to understand how these can move beyond the digital to face-to-face relationships and action.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Crucially, key actors within each Group had high level of social media self-efficacy (Hocevar et al, 2014) and were known for transparent and tactful way of tackling issues affecting the community. Their dedicated voluntary engagement proved essential for shaping the Groups to become self-managing entities.…”
Section: Discussionmentioning
confidence: 99%
“…Many people with high levels of social media use, come to depend on social media for information. These people may be described as having social media self-efficacy (Hocevar et al, 2014) and they find the opinions of those on social media to be trustworthy, and they relying on them when making decisions in their lives. However, the potential of a residential community of practice to develop collective learning using social media is not yet recognised within the building industry.…”
Section: Best-practice In the Homementioning
confidence: 99%
“…This study looks at PBC in the context of confidence and certainty of being able to use SNSs when organising trips. Studies by Baker and White (2010), Hocevar, Flanagin and Metzeger (2014) as well as Leng et al (2011) have found that PBC (self-efficacy) exerts significant positive influence attitude towards the use of SNSs. Accordingly, it is hypothesised in this study that:…”
Section: Perceived Behavioural Controlmentioning
confidence: 99%